Self-surveillance and power: perspective gazes of mobile-health - Meola, Lorella (Medicina e Morale, 2020)
Mobile-health is an increasing field of digital technologies realized in order to cure illness, promote health and wellness. In particular, it is a useful solution for disease prevention and chronic diseases management. However, these technologies arise several ethical and regulatory concerns because of the wide and varied field of mobile-health technologies and their several specific purposes. This paper analyzes the ethical and political implications arising from mobile-health's hybrid definition, to the edge of health promotion and lifestyle management, proving it as a strategy that takes individual lives. Based on self-surveillance, mobile-health gathers data from each one and gives recommendations to every individual, in order to have healthy behaviours. It comes to datification and modulation of the conducts, aiming to optimize life, that is vital functions' maximization. Optimization could make human conduct a set of proliferating performances, through which individuals would make themselves better and better, but, so doing, they could turn into a social, political, economic means for social growth. We are going to prove that self-surveillance, mobile-health's main strategy, could turn into a heteronymous government of the conducts.